Genre and interpretation - Lyytikäinen, Pirjo; Klapuri, Tintti; Maijala, Minna (Department of Finnish, Finno-Ugrian and Scandinavian Studies & The Finnish Graduate School of Literary Studies, 2010)
Lyytikäinen, Pirjo: Introduction ; McHale, Brian: Science fiction, or, the most typical genre in world literature ; Nünning, Ansgar: Genre theory matters : criteria for defining and classifying genres and a typology of historical novels and other narrative genres ; Nünning, Vera: Relevance of generic frames for the interpretation of novels ; Pettersson, Bo: On the interrelation of genre and mimesis, especially in science fiction and realist fiction ; Locatelli, Angela: "I give you my word(s)" : layered realism and images of life literature ; Isomaa, Saija: Genre theory after linguistic turn : an anti-essentialist, hermeneutic approach to literary genres ; Ameel, Lieven: Road to Helsinki : the young provincial and the confrontation with the city in Juhani Aho's Helsinkiin (1889) and Finnish literature at the turn of the the Twentieth Century ; Juntunen, Tuomas: Waiting for nothing significant? : tragedy as subtext in Juha Seppälä's novel Yhtiökumppanit ; Klapuri, Tintti: Naturalistic worldview in Chekhov's non-fiction : social adaption and intertwining discourses in Sakhalin Island ; Lival-Juusela, Maria: From the margin of Finland's Swedish literature toward identifying the female bildungsroman ; Mäkelä, Hanna: "Imitators and observers" : mimetic and elegiac character relationships in Donna Tartt's The secret history and Siri Hustvedt's What I loved ; Nakari, Netta: Confessing passion in Annie Ernaux's Passion perfect